Gestión administrativa del servicio de agua potable Municipal de la Parroquia Caracol EMSABA EP - Cuadro Montoya, Ramon Angel (2019)
urrently, the Municipal Public Company of Environmental Sanitation of Babahoyo, EMSABA-EP, is a company dedicated to services goods whose objective is the administrative management and the techniques of the necessities inhabitant in the provision of services and supply of drinking water, treatment system and discharge of sewage, sanitary sewerage, storm drainage, flood control, collection and management of its disposal with the start of construction in 1994. In the rural sectors a bad administration is carried out by the authorities of the company EMSABA E.P in the treatment of the drinking water service. One of the faculties that corresponds to the Municipality is to provide an excellent quality service for the user and improve administrative management for the provision of drinking water service in rural areas. According to (Palomo Martinez, 2014, page 102) Quality in most products and services the purchase decision is not strictly guided by the price. Although the product is physically the same, the customer may perceive it as different depending on the quality of the service it receives. To improve the drinking water service, many factors must be improved, such as the administrative management of the Autonomous Decentralized Governments of the Caracol Parish together with the Babahoyo Mayor's Office, taking into account the use